Let it Grow (Back): A Call for the Conservation of Secondary Forests as Medicinal Plant Habitat - Daniela J. Shebitz; Lindsey Page Agnew; Steven Kerns; Angela Oviedo; Juyoung Ha (Ethnobiology Letters, 2023)
Costa Rica is widely regarded as a global leader in conservation practices. In the Maquenque National Wildlife Refuge (MNWLR), within Costa Rica’s Northern Zone, a strong commitment to conservation has led to protecting highly biodiverse mature forests. However, a significant opportunity to strengthen conservation in this region is being overlooked at a great cost to the local community and environment: the protection of regenerating secondary forests. Secondary forests account for over 50% of global tropical forests and serve vital ecological and cultural functions. Within the MNWLR, many species in the secondary forests provide medicinal value to the rural communities where western medical care is difficult to access. Recent research, however, has shown that secondary forests in Costa Rica are re-cleared within 20 years, before they have accumulated the previously lost biomass and biodiversity. In this paper, we call for conservation and management strategies to incorporate community held knowledge about culturally significant species, and for there to be economic incentives for keeping secondary forests intact and for determining which forests are designated as Protected Areas. We discuss previous research with two trees that are common in secondary forests in the MNWLR (Vismia macrophylla and Pentaclethra macroloba), recognizing that these are some of the many species that have great potential to both the ecological and social communities. While our focus area is in the Northern Zone of Costa Rica, the integration of community use and local knowledge into conservation should be a global priority.